Efeito da dieta hipercalórica e hiperlipídica rica em gordura poliins aturada, ômega 3 e 9, na formação de criptas aberrantes em mucosa cólica, induzidas por azoximetano em ratos - Burlamaqui, Idália Maria Brasil (2008)
Colorectal câncer is the fifth most common type of câncer in Brazil and the incidence is growing in developed countries. The earliest preneoplastic lesion presenting dysplasia is aberrant crypt foci (ACF), a precursor of colorectal adenoma and câncer in humans. Knowledge of ACF formation is crucial to understanding the mechanisms involved in colorectal câncer and their inhibition. The objective of this study was to determine whether a hypercaloric, hyperlipidic diet (HCD) affects azoxymethane (AOM)-induced ACF formation in rat colonic mucosa. Thirty-six 8-week old male Wistar rats weighing 180-250g were distributed into 4 groups of 9 animais each: Group I: HCD without AOM; Group II: normocaloric diet (NCD) without AOM; Group III: HCD and AOM; Group IV: NCD and AOM. From the eighth week onwards the animais in Groups I and III were fed HCD (4,250 cal/kg; rich in polyunsaturated fat; ratio co6:co3=3:l, with addition of fiber, minerais and vitamins). The animais in Groups II and IV were fed NCD (3,000 cal/kg). At 16 weeks, the animais in Groups III and IV were injected i.p. with 15 mg/kg AOM once a week for 2 weeks, while the animais in Groups I and II received 0.9% physiological saline. At 15 weeks after AOM or saline administration, the animais were euthanized and their weight, clinicai changes, adenomas, ACF and number of crypts per focus (multiplicity) according to colon section (proximal, middle or distai) were registered. The fíndings were submitted to variance analysis and the levei of statistical significance was set at 5% (/?<0.05). HCD was found to promote weight increase in Group III compared to Group IV. No significant increase in the total number of ACF was observed for the middle and distai segments (p=0.985 and />=0.854, respectively). The multiplicity of foci with 1-4 aberrant crypts was similar for tfle middle and distai segments (p=0.499 and p=0.244, respectively). The corresponding figures for foci with >5 aberrant crypts were £>=0.471 and £>=0.820. The total number of ACF in the colonic mucosa differed significantly between Group IV and Group III (%2 = 4.091; £>=0.043). It may thus be concluded that HCD promotes weight increase and, while not affecting the total number of ACF, reduces the proportion of foci with >5 aberrant crypts, thereby indirectly preventing the emergence of preneoplastic lesions in rat colonic mucosa.